Claypeyrons Theorem
Claypeyrons Theorem
Claypeyrons Theorem
24.1 Introduction
A beam having many supports and covering more than one span is called continuous beam. It
is nothing but a simple beam extended over many supports on either side and consisted of
many spans. A continuous beam must have a minimum of two spans and three supports. The
ends of the continuous beam may be either fixed or propped. The length of spans of a
continuous beam may be either fixed or propped. The length of spans of a continuous beam
may be either equal or unequal. Similarly, the moment of inertia in various spans may be
same or different. A continuous beam is statically indeterminate. Owing to the continuity of
the beam over the supports, bending moments will exist at these supports. Until these bending
moments are known, the bending moment diagram (BMD) and the shear force diagram
(SFD) can not be drawn.
A continuous beam can be analysed by various methods. A more general method was
proposed by Clapeyron. This is called Clapeyron’s theorem of three moments.
In this method we develop an expression for the slope of the beam at a support, say, at B in
Figure 24.1 in terms of both known and unknown bending moments, considering first span
AB and then span BC as shown in Figure 24.1. Both the expressions thus developed represent
one and the same aspect, namely, the slope of the beam at B. Hence they are equal and result
in an equation connecting the values of the bending moments at A, B and C. If we apply in
turn this methodology to each support over which the beam is continuous, we can get a
sufficient number of equations to evaluate all the unknown bending moments, provided that
the bending moment is zero at two extreme supports if they are pinned or the bending
moments at two supports are known otherwise or can be determined from the conditions of
the problem.
Once we determine the bending moment at all supports, the BMD and the SFD for the beam
can be drawn.
Let us consider a two span continuous beam as shown in Figure 24.2. on which a general
loading acts. We assume EI to be constant throughout.
The span of AB is L1 and that of BC is L2. The BMD on a corresponding simple beam is
shown in Figure 24.2 (b). The fixed end moments MA, MB and MC are the support moments
at A, B and C respectively (Fig 24.2 (c)). In Fig 24.2 (b), a1 is the distance of the center of
gravity (CG) of the area of the BMD for the span AB from the end A and a2 is the
corresponding quantity for the span BC from the end C. In Fig 24.2 (c), a1 is the distance of
the CG of the area of the support moments for the span AB from the end A and a 2 is the
distance of the corresponding area for the span BC from the end C.
Let us first consider AB. The bending moment at any section distance x from A due to
applied loading as shown in Figure 24.2 (b) is given by Mx. Therefore, the net moment at that
section is given by Mx-Mx’. From the fundamental bending equation,
d2y
EI 2 = M x − M x' (a)
dx
Multiplying both sides of eq(a) by x
d2y
EIx 2 = xM x − xM x' (b)
dx
Integrating Eq. (b) from 0 to L1, we obtain
L1 L L
d2y 1 1
∫0 dx 2 = ∫0 x x ∫0 xM x d x
− '
EIx dx xM d (c)
L
dy
1
EIx x − y = A1 a1 − A1 a1 (d)
dx 0
L1
Where A1 is the area of the BMD for the span AB and is given by ∫M
0
x dx and A1a1 is the
L1
holds good for support moments for the span AB and is equal to ∫ xM
0
x dx .
A1 a1 =
1
(M A + M B )L1 × (M A + 2M B )L1 = 1 (M A + 2M B )L12 (j)
2 (M A + M B )3 6
Substituting Eq (i) into eq (g),
L12
EIL1θ B = A1 a1 − (M A + 2 M B )
6
6 EIθ B = 6 A1 a1 / L1 − L1 (M A + 2 M B ) (k)
Similarly, we can consider the span BC and take C as the origin, with x positive to the left
and it can be derived that
6A a
6 EI (− θ B ) = 2 2 − L2 (M C + 2M B ) (l)
L2
As the directions of x from A in the span AB and from C in the span BC are of the opposite
nature, the value of the slope at B, θ B will have the opposite sign for the span BC. Therefore
Eq(1) becomes
6 A2 a 2
− 6 EIθ B = − L2 (M C + 2M B ) (m)
L2
Addition of Eqs (k) and (m) yields
6A a 6A a
0 = 1 1 − L1 (M A + 2M B ) + 2 2 − L2 (M C + 2M B )
L2 L2
6A a 6A a
= 1 1 + 2 2 − L1 M A − 2 L1 M B − L2 M C − 2 L2 M B
L2 L2
6 A1 a1 6 A2 a 2
L1 M A + 2 L1 M B + L2 M C + 2 L2 M B = +
L2 L2
6A a 6A a
M A L1 + 2 M B (L1 + L2 ) + M C L2 = 1 1 + 2 2 (24.1)
L2 L2
Equation (24.1) is the Clapeyron’s theorem of three moments which can be used to solve
problems on continuous beams of varying span lengths, different moments of inertia and
subjected to different types of loading. The three moment equation expresses the relation
between the bending moments at three successive supports of a continuous beam subjected to
a certain applied loading on different spans.
25.1 Introduction
In this lecture, some example problems will be discussed. The Table 25.1 shows the
values of and for standard loading
6A a 6A a
Table 25.1 Values of 1 1 and 2 2 for standard loading
L L
Sl Type of loading 6 A1 a1 / L 6 A2 a 2 / L
N
o
1 wL3 / 4 wL3 / 4
2 (
α 22 2 L2 − α 22
w / 4L
) (
β 22 2 L2 − β 22 )
2
w / 4L 2
2 2
(
− α 1 2 L − α 1 ) (
− β1 2 L − β 1
2 2
)
3 (8 / 60)wL3 (7 / 60)wL3
4 (7 / 60)wL3 (8 / 60)wL3
5 (5 / 32)wL3 (5 / 32)wL3
7 [
− (M / L ) 3(L − α ) − L2
2
] [
+ (M / L ) 3α 2 − L2 ]
Example 1:
Analyse the beam as shown in Figure 25.1 below with constant EI using Clapeyron’s three
moment equation.
Solution:
The continuous beam is shown in Fig. 25.1. We denote the left support as A, middle support
as B, and right support as C. MA = MC = 0 because the supports are simple. From Table
25.1,
6 Aa 7
For the left span = × 5 × 4 3 = 37.33KNm 2
L 60
6 Aa 5
For the right span, = × 3 × 3 3 = 12.66 KNm 2
L 32
6 A1 a1 6 A2 a 2
From the expression M A L1 + 2M B (L1 + L2 ) + M C L2 = + , we have
L2 L2
2M B (4 + 3) = 37.33 + 12.66
M B = 3.57 KNm
Example 2:
The moment of inertia of s continuous beam is different for different spans as shown in
Figure 25.2 . Find the reactions.
Solution:
The beam with M.I. different for different spans is shown in Fig. 25.2. From left to right
supports are denoted as A, B, and C, respectively.
6 Aa 6 × 3 3 18
= =
I 1 L1 3I × 3 I
9 ×1 2
6 Aa
=
I 2 L2 5I × 3
(3 − 12 =) 4 .8
I
3 3 18 4.8
2M B + = +
3I 5 I I I
Example 3: Draw the SFD and BMD for the continuous beam shown in Figure 25.4.
Solution:
The two span beam is shown in Fig. 25.4. We denote the supports as A, B, and C.
6 Aa 5 × 12 × 6 3 270
= =
I 1 L1 1.5 I × 32 I
6 Aa 20 × 5 3 285.71
= =
I 2 L2 1.75 I × 5 I
6 A1 a1 6 A2 a 2
M A L1 + 2M B (L1 + L2 ) + M C L2 = +
L2 L2
6 5 270 285.71
2M B + = +
1.5 I 1.75 I I I
M B = 40.53KNm
The reactions have been calculated in Figure 25.5.
The SFD is shown in Figure 25.5 (b) and the BMD is shown in Figure 25.5 (c).
In this Lecture, some example problems on other indeterminate beams will be discussed.
Example 1: Using Clapeyron’s theorem, solve the problem of the continuous beam as shown
in Figure 26.1. EI is constant throughout.
Solution:
The three span continuous beam is shown in Fig. 26.1. The left end of the beam is fixed. Now
we insert an imaginary span to the left of A as shown in Fig. 26.1(a).
6 Aa 9 × 3 3
= = 60.75 KNm 2
L 4
From the expression
6 A1 a1 6 A2 a 2
M A L1 + 2M B (L1 + L2 ) + M C L2 = +
L2 L2
2M A (0 + 3) + M B × 3 = 60.75
6M A + 3M B = 60.75
2M A + M B = 20.25 (a)
6 A1 a1 6 A2 a 2
Again from expression M A L1 + 2M B (L1 + L2 ) + M C L2 = +
L2 L2
M A × 3 + 2 M B (3 + 3) + M C × 3 = 60.75
M A + 4 M B + M C = 20.25 (b)
6 Aa 12 × 15 2
From Table 25.1 for span CD,
L
=
3
( )
3 − 1.5 2 = 40.5 KNm 2
MD =0
6 A1 a1 6 A2 a 2
From expression M A L1 + 2M B (L1 + L2 ) + M C L2 = +
L2 L2
M B × 3 + 2 M C (3 + 3) = 40.5
M B + 4 M C = 13.5 KNm 2 (c)
Solving (a), (b) and (c), we get MA = 9.09 kNm, MB = 2.08 kNm, MC = 2.86 kNm.
Problem 2: A continuous beam has overhangs on both sides as shown in Figure 26.2 below.
Apply three moment equation to determine the support moments. EI is constant throughout.
Solution:
The continuous beam with double overhangs is shown in Fig. 26.2. We denote the left
support as A, middle support B and right support C. The UDL on left overhang will transfer a
moment = 2 × 1 × 0.5 = 1 kNm to the left support. Similarly, the concentrated load on right
overhang will transfer a moment = 5 × 0.5 = 2.5 kNm to the right support. For the loaded
span from Table 25.1,
(
6 Aa 3 × 1.5 × 2.5 2 − 12
=
)
= 9.45 KNm 2
L 2 .5
(
6 Aa 2 × 1 × 21 − 12
=
)
= 3KNm 2
L 2
6 A1 a1 6 A2 a 2
From expression M A L1 + 2M B (L1 + L2 ) + M C L2 = +
L2 L2
1× 2.5 + M B (2.5 + 2) + 2.5 × 2 = 9.45 + 3
M B = 1.1KNm